2020
DOI: 10.1002/stem.3150
|View full text |Cite
|
Sign up to set email alerts
|

Using umbilical cord blood for regenerative therapy: Proof or promise?

Abstract: The identification of nonhematopoietic progenitor cells in cord blood has spawned great interest in using cord blood cells for new indications in regenerative therapy.Many preclinical studies demonstrated improvement in reperfusion and markers of organ recovery using cord blood-derived cells in a range of animal models. Initial results heralded increasing clinical interest regarding the use of cord blood for regenerative therapy. Initial clinical studies were largely uncontrolled feasibility studies that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Umbilical cord blood (UCB) is an attractive source of mesenchymal stromal cells because of its abundance and relative ease of collection. Some studies have demonstrated that primitive human umbilical cord blood-derived MSCs (hUCB-MSCs) have biological advantages over bone marrow or adipose tissue, which suggests that hUCB-MSCs are a useful model for clinical applications of cell therapies [ 18 , 19 ]. Furthermore, hUCB-MSCs cultured with specific substances produce growth factors and regulatory factors that have paracrine effects on surrounding cells.…”
Section: Introductionmentioning
confidence: 99%
“…Umbilical cord blood (UCB) is an attractive source of mesenchymal stromal cells because of its abundance and relative ease of collection. Some studies have demonstrated that primitive human umbilical cord blood-derived MSCs (hUCB-MSCs) have biological advantages over bone marrow or adipose tissue, which suggests that hUCB-MSCs are a useful model for clinical applications of cell therapies [ 18 , 19 ]. Furthermore, hUCB-MSCs cultured with specific substances produce growth factors and regulatory factors that have paracrine effects on surrounding cells.…”
Section: Introductionmentioning
confidence: 99%
“…Umbilical cord blood is a rich source of stem cells that can be used in treatments for blood and immune system disorders. It is also used for research into novel therapies not yet ready for clinical application [1,2]. The use of the stem cells in these applications depends on individuals banking their cord blood in either public, private, or public-private hybrid banks.…”
Section: Background -The Problemmentioning
confidence: 99%
“…The Supreme Court of Canada has addressed the legal meaning of a general impression in the context of Quebec's Consumer Protection Act, a provincial statute that is largely based on the Competition Act. In Richard v. Time, Inc, the Supreme Court held that assessing a general impression requires "describing the general impression that the representation is likely to convey to a "credulous" and inexperienced consumer; and [2] determining whether that general impression is true to reality" [59].…”
Section: Truth In Advertisingmentioning
confidence: 99%
“…Even if the autologous bone marrow and adipose tissue-derived mesenchymal stromal cells (BM-MSCs and AT-MSCs, respectively) are the most prevalent well-accepted cells in clinical trials [17,18], the invasiveness of collecting samples in both procedures has led scientists to find other sources of MSCs. For example, extraembryonic tissues, such as placenta [19], amniotic membrane [20][21][22], and umbilical cord [23][24][25], which are usually intended as discards of childbirth, have recently been considered new emerging sources. MSCs isolated from human term amnion (hA-MSCs) meet all the release minimal criteria [26,27] but, compared with MSCs isolated from bone marrow, the placental-derived MSCs have been reported to proliferate faster and more robustly during expansion in in vitro cultures [18].…”
Section: Introductionmentioning
confidence: 99%